2016
DOI: 10.1007/s13762-015-0921-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance of microbial-induced carbonate precipitation on wind erosion control of sandy soil

Abstract: Wind erosion is a serious problem throughout the world which results in soil and environment degradation and air pollution. The main objective of this study was to evaluate feasibility of microbial-induced carbonate precipitation, as a novel soil-strengthening technique, to reduce wind erosion risk of a sandy soil. For this purpose, the erosion of biocemented soil samples was investigated experimentally in a wind tunnel under the condition of wind velocity of 45 km h -1 . The weight loss of treated samples rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…A reduction in the total erosion mass upon MICP treatment has also been reported, due to bacteria-cementation reagent-related substances, i.e., calcite precipitates, which are not only harmless but also effective and environmentally friendly [179]. Similarly, there was a reduction in mass loss due to erosion in the treated soil when compared with the natural soil [180]. These reductions were not directly proportional to the volume of bacterial suspension density used, being mainly due to the calcite precipitates formed [180].…”
Section: Liquefaction Mitigation and Erosion Controlmentioning
confidence: 83%
See 1 more Smart Citation
“…A reduction in the total erosion mass upon MICP treatment has also been reported, due to bacteria-cementation reagent-related substances, i.e., calcite precipitates, which are not only harmless but also effective and environmentally friendly [179]. Similarly, there was a reduction in mass loss due to erosion in the treated soil when compared with the natural soil [180]. These reductions were not directly proportional to the volume of bacterial suspension density used, being mainly due to the calcite precipitates formed [180].…”
Section: Liquefaction Mitigation and Erosion Controlmentioning
confidence: 83%
“…It was also reported [175,176] that the use of MICP treatment can completely alter the liquefaction failure mode from flow failure to cyclic mobility, and significantly vary the excess pore pressure generation response of initially loose specimens. Erosion mitigation using MICP has also been reported [177][178][179][180]; while they differ in the methods adopted, most studies have reported the mass loss and penetration resistance. The suppressive ability of MICP for controlling wind erosion has recently been studied by subjecting MICP-treated soils to wind tunnel conditions at different intervals, after which the mass loss due to erosion was determined.…”
Section: Liquefaction Mitigation and Erosion Controlmentioning
confidence: 99%
“…ICGRE 149-7 Maleki et al [19] conducted wind erosion tested using MICP solution varying the concentration of the cementation solution (both urea and calcium chloride concentration). The soil resistance to erosion increased with the increase in the cementation solution.…”
Section: Fugitive Dust Control Using Urease-aided Calcium Carbonate Pmentioning
confidence: 99%
“…Agronomic methods including means of fencing and planting plants represent an environmentally friendly and aesthetically pleasing way to reduce wind erosion. However, they have some associated limitations because agronomic methods would not work on soils that are agriculturally unsuitable (Maleki, Ebrahimi, Asadzadeh, & Tabrizi, ; Mcclure, ). In addition, these methods require an extensive growing period and are not suitable for agricultural application in arid and dry lands (Diouf, Skidmore, Layton, & Hagen, ).…”
Section: Introductionmentioning
confidence: 99%